97 Health problem of indian farmers due to excessive heat exposure and preventive measures. (24th April 2018) - Kesarwani, K; Sharma, P
Abstract : Introduction: India is primarily an agrarian economy as farming is one of the most important occupations in country. However numbers of studies have classified farming as a risky and hazardous job because of the nature of farm work. Farm workers are particularly at higher risk of developing health problems. The drastic change in the world wide climate has created too much problems among farmers. Most of farm operations in India are still accomplished manually under direct sunshine. These entire factors, makes farm operation quite dangerous. The exposure to hot occupational environment remains a persistent impediment to improve productivity and problems affecting health. Health problems that result from heat stress are known as heat disorders. Methods: The study was undertaken to find out the health problems experienced by farmers and to design, develop and disseminate PPE to safe guard farmers from the impact of excessive heat. Results: It was revealed that majority of farmers were working for more than 7 hours in squatting and bending position under direct sunshine which was promoting heat disorders resulting from heavy physical work leading to loss of fluid and salt resulting in heat cramp, heat exhaustion, etc, . Prevalence of above factors is more common among farmers due to unawareness and lack of knowledge about associated heat exposure risks, leading to poor adaption of preventive and protective measures. Further, incidence of MSDs among the farmers was reported by majority. The long working hours and posture adopted resulted more in body pain/discomfort. While disseminating the PPE, the acceptability among the farm workers was reported to be very high. Conclusion: The pace with which global average temperature is rising, there arise a need to protect the outdoor workers from heat-related illnesses. Creating awareness and developing of PPE to safeguard has now become a matter of concern worldwide.